THE EFFECT OF USING SONG ON THE FOURTH-GRADE STUDENTS’ LEARNING MOTIVATION IN NATURAL SCIENCE LEARNING SUBJECT AT FREE METHODIST 2 PRIVATE ELEMENTARY SCHOOL MEDAN - Rosari Hotma J. Simbolon; Bogor Lumbanraja; Patri Janson Silaban; Antonius Remigius Abi; Dewi Anzelina (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2023)
This study examines the effect of using songs as learning media on fourth-grade students’ learning motivation in Natural Science subjects at Free Methodist 2 Private Elementary School, Medan, during the 2022/2023 academic year. The research employed an experimental method with a population of 84 fourth-grade students distributed across three classes. A purposive sampling technique was applied, selecting class IV C as the research sample, consisting of 30 students. The findings indicate that students’ learning motivation when using song-based media falls into the high category, with an average score of 79.23. The correlation analysis yielded a coefficient of 0.865, where the calculated r-value exceeded the r-table value (0.865 ≥ 0.361), leading to the acceptance of the alternative hypothesis. Furthermore, the results of the t-test demonstrate a significant effect of song media on students’ learning motivation, as shown by the calculated t-value being greater than the t-table value (9.123 ≥ 1.071). These results confirm that the use of song media has a positive and significant influence on fourth-grade students’ motivation in learning Natural Science at Free Methodist 2 Elementary School, Medan, in the 2022/2023 academic year.